2020
DOI: 10.1021/acssuschemeng.9b06936
|View full text |Cite
|
Sign up to set email alerts
|

Hamamelis-like K2Ti6O13 Synthesized by Alkali Treatment of Ti3C2 MXene: Catalysis for Hydrogen Storage in MgH2

Abstract: An intriguing Hamamelis-like structure of K2Ti6O13 with branches of 10–20 nm in length is synthesized by alkali treatment of Ti3C2 MXene. It exhibits strong catalytic activity for hydrogen desorption from MgH2. The initial dehydrogenation temperature (175 °C) of a composite of MgH2 with 5 wt % K2Ti6O13 is 112 °C below that of pristine MgH2. Isothermal dehydrogenation analysis indicates that the composite releases 6.7 wt % hydrogen at 280 °C within 3 min, and with 2.7 wt % hydrogen being released at 200 °C. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…MXenes have shown possible applications in energy conversion and storage and catalysis. MXenes and their derivatives also have positive effects on the hydrogen storage materials. In 2016, Liu et al made the first attempt to utilize two-dimensional Ti 3 C 2 to significantly enhance the hydrogen sorption behavior of MgH 2 . It was shown that MgH 2 –5 wt % Ti 3 C 2 starts releasing hydrogen at 185 °C and can reach a capacity of 6.2 wt % within 60 s at a constant temperature of 300 °C, while it can absorb 6.1 wt % of hydrogen in 30 s at a temperature of 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes have shown possible applications in energy conversion and storage and catalysis. MXenes and their derivatives also have positive effects on the hydrogen storage materials. In 2016, Liu et al made the first attempt to utilize two-dimensional Ti 3 C 2 to significantly enhance the hydrogen sorption behavior of MgH 2 . It was shown that MgH 2 –5 wt % Ti 3 C 2 starts releasing hydrogen at 185 °C and can reach a capacity of 6.2 wt % within 60 s at a constant temperature of 300 °C, while it can absorb 6.1 wt % of hydrogen in 30 s at a temperature of 150 °C.…”
Section: Introductionmentioning
confidence: 99%
“…As clearly shown in the gure, the MgH 2 + 5Na , respectively. Subsequently, the dehydrogenation dynamics were investigated according to the nine kinetic models proposed in our previous report 24 . It should be noted that f(α) = A(t/t 0.5 ), where t 0.5 is the time when α = 0.5 and A is a constant depending on the kinetic model, and f(α) is a term for the reaction rate depending on the reaction mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Among all catalysts investigated, Ti-based materials are commonly recognized as the best-performing ones and have been widely used to improve the hydrogen storage performances of the MgH 2 system, via signi cantly reducing the activation energy of de/ab-hydrogenation of MgH 2 while unchanging the enthalpy and entropy in the hydride formation process 22 . In particular, titanate materials, such as NiTiO 3 23 , K 2 Ti 6 O 13 24 , TiVO 3.5 25 , etc., have attracted more attentions in MgH 2 hydrogen storage system.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen storage materials have drawn significant attention because of their importance in the development of sustainable energy. In recent years, the hydrogen isotopes storage materials for handling the fuels (deuterium and tritium) of a nuclear fusion system in the International Thermonuclear Experimental Reactor (ITER) are extracting extensive research. ZrCo alloy is considered as the most promising material to be used in a hydrogen isotopes storage and delivery system (SDS) in ITER due to its excellent hydrogen storage performances, , such as low equilibrium hydrogen pressure under room temperature, prominent de-/hydriding kinetics, and moderate desorption temperature for the delivery of 100 kPa hydrogen.…”
Section: Introductionmentioning
confidence: 99%